Quality h[videorecording] : total customer service (London : Taylor Made Film, 1992)
The video talks on how to give customer service by meeting customer's need
Part I. Lampeter & Son (16 min.) - Part II. Case studies ; featuring British Gas, Digital, Texaco (45 min.)
Keywords: Customer services; Customer relations; Customer services -- Case studies